Analisis Windrose Sebagai Input Sofware AERMOD - Risma Nopita; Aryo Sasmita; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The operation of Tembilahan Coal-fired Power Plant produces emissions, one of which is SO2. The SO2 pollutant emissions can have an impact on the environment as well as on health. To find out the distribution of SO2 emissions more specific the surrounding area, a modeling using AERMOD View software is performed. Modeling is carried out within one year by doing windrose analysis. The results of the simulation show that the pattern of SO2 emissions distribution from Tembilahan Coal-fired Power Plant in 2018 - 2019 tends to move from northeast to southwest from its source. The distribution of SO2 from the sources is affected by the characteristics of the wind direction. Keywords: AERMOD View, SO2, Coal-fired Power Plant